د پوهاند فضل ولي ناګار شاعرۍ کې حماسي او عرفاني مفاهیم - Miyakhil, Mohammad Hussain Miyakhil (Farah Research and Scientific Journal, 2024)
Pohand Fazel Wali Nagar, who has been a co-writer and writer in Afghanistan's contemporary Islamic literature, can be said to have a strong belief and definite ambition. Besides being a teacher, he is also a revolutionary and a wise poet. The humorous moments have been decorated and saved in a special style in beautiful poetry and songs with great elegance and delicacy. It is necessary to research it, the purpose here is to introduce the poet's poetry after knowing the mysticism and mysticism of the poem, and then to analyze the examples of mysticism and mysticism in the poems of the pohand, which is a kind of bibliographic research. And the explanatory method will be found in the report, that the professor has analyzed the internal qualities in a very expert manner, besides this, in this research, the readers are presented with detailed explanations about the mysticism and mysticism. In the poetry of Pohand Nagar, examples of epic and mystical concepts have been presented. In the poetry of Pohand Nagar, rare analogies and imagery have been found, which convey the concepts mentioned to the readers in a very interesting way. Another important finding is that Pohand has chosen a dramatic path for his mysticism Irfan and Sufism can add a new discussion to the concept.